Diagnostically misleading aberrant terminal deoxynucleotidyl transferase expression in germ cell tumors - Pęksa, Rafał; Kunc, Michał; Bieńkowski, Michał; Popęda, Marta; Biernat, Wojciech (Polish Journal of Pathology, 2022)
Terminal deoxynucleotidyl transferase (TdT) is a unique type of DNA polymerase predominantly expressed in precursor lymphoid cells and acute lymphoblastic leukemia. It participates in the junctional diversity of T-cell receptors and immunoglobulins. Recently, aberrant TdT expression was found in seminomas. Here, we evaluated the expression of TdT in our cohort of germ cell tumors (GCTs) with two anti-TdT antibody clones. We included 173 cases of testicular GCTs, 5 ovarian dysgerminomas, and one gonadoblastoma in the study. Tissue microarrays containing representative tumor samples were constructed and subsequently stained with anti-TdT monoclonal rabbit antibody EP266 (Dako) and TdT rabbit polyclonal antibody (Cell Marque). Expression was assessed with the H-score. No specific nuclear reaction was observed for the polyclonal anti-TdT antibody. The H-score values varied between the histological subtypes for the EP266 antibody. Positive nuclear staining was consistently seen in germ cell neoplasia in situ , seminoma, dysgerminoma, and embryonal carcinoma. Pure tumors had higher TdT H-scores than the mixed ones. Teratomas, yolk sac tumors, and choriocarcinomas were almost uniformly negative. Our study confirms that aberrant expression of TdT by testicular and ovarian GCTs exemplifies a potential diagnostic pitfall in histopathological diagnostics.